Antidiabetic Activity of Hydroalcholic Extract of Herbal Marketed Product Madhuhari Churna in Alloxan - Induced Diabetic Rats - Mansoory, Nazar (International Journal of Pharmaceutical & Biological Archive, 2010)
Hypoglycemic and antidiabetic activity of hydroalcoholic extract of Madhuhari churna was evaluated in alloxan induced diabetic rats. Effect on normal blood glucose level (hypoglycemic), Oral glucose tolerance test (OGTT), hyperglycemia (antidiabetic) and glycogen level in liver was evaluated. Hydroalcoholic extract was administered orally at two dose levels 200 mg/kg and 400 mg/kg body weight, for consecutive 10 days in diabetic rats, and glibenclamide was kept as standard. Blood glucose (BG) and OGTT in normal healthy rats produced significant fall in BG and improved glucose tolerance. The present study concludes that the Madhuhari churna is effective in reducing the blood glucose level of diabetic animals. The extract did not exhibit a dose dependent effect.